Penafsiran Konsep Konten Youtube sebagai Bentuk Aset yang Bisa Diikat oleh Fidusia Dalam Tinjauan Hukum Ekonomi Syariah - Nurcahyo, Febry Wahyu (Institut Agama Islam Negeri Metro, 2023)
The government currently supports creative business actors by providing facilities for designing intellectual property rights financing, with the aim of enabling creative entrepreneurs, especially YouTubers, to use their YouTube channel copyrights as collateral through financial institutions such as banks and non-banking institutions. This research discusses the legal regulations related to copyright that apply to YouTube channels as objects of fiduciary guarantees and identifies the obstacles in making YouTube channels eligible for such guarantees. The study uses a normative legal research approach, supported by a literature study. The research methodologies include the statutory approach, conceptual approach, and Sharia economic law analysis. Secondary data was obtained through library research. The findings from the literature review conclude that YouTube channel copyrights have the potential to be used as objects of fiduciary guarantees in accordance with the provisions set forth in Article 16 of Law Number 28 of 2014 on Copyright, Law Number 42 of 1999 on Fiduciary Guarantee, and Government Regulation Number 24 of 2022 on the Provisions for the Implementation of the Creative Economy.